Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Kosumen Di Toko EIGER Pangkal Pinang Influence Of Product Quality And Price On Customer Satisfaction At The EIGER Shop In Pangkal Pinang - Yogi .; Kartina . (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2019)
Product quality and price are one of the important factors in an effort to improve the quality of the company. Business people with product quality and good pricing will be very easy in business competition in the era of globalization. This study aims to find out the importance of products quality and prices to building long-term relationships with customers at the Eiger Shop in Pangkal Pinang City. The sample in this study amounted to 35 respondents who bought products at the Eiger shop in Pangkalpinang city. Sampling method is used purposive sampling with data collection methods is using questionnaires. The analysis technique is used descriptive analysis by integrating qualitative. The results of this study indicate product quality and prices has positive and significant influence on customer satisfaction. In this study it was also found that customer satisfaction can build long relationships with customers